EKSPLORASI MANIPULATING FABRIC RUFFLE INSPIRASI APHRODITE PISCES PADA READY TO WEAR DELUXE - Patimah, Cucu; Marlianti, Mira; Djuniwarti, Djuniwarti (Institut Seni Indonesia Padangpanjang, 2024)
Manipulating fabric is a technique in engineering textile materials to produce new textile materials which aim to beautify clothing, one of which is through the ruffle technique which can be applied to create a wrinkled effect on the fabric so that it produces a new visualization, namely making it wavy and voluminous. The work highlights the zodiac Pisces, which is symbolized by a pair of fish swimming in opposite directions. Pisces is a zodiac sign born on February 18-March 19. This zodiac sign is considered to be a person who likes adventure and has a great imagination. According to Greek mythology, these two fish are Aphrodite. Aphrodite is the symbol of the most beautiful Greek goddess who is the goddess of love and beauty. Due to the nature of Pisces, which has unlimited imagination, the creator uses a creation method consisting of exploration, experimentation and realization. The results of this work are six RTW Deluxe in the evening gown category which will be presented in the form of a fashion show at the Jogja Fashion Parade 2024 event.